2021
DOI: 10.1098/rstb.2020.0139
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of ideological differences in race categorization

Abstract: Multiracial individuals are often categorized as members of their ‘socially subordinate’ racial group—a form of social discrimination termed hypodescent—with political conservatives more likely than liberals to show this bias. Although hypodescent has been linked to racial hierarchy preservation motives, it remains unclear how political ideology influences categorization: Do conservatives and liberals see, feel or think about mixed-race faces differently? Do they differ in sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The present results, therefore, offer a novel addition to this literature by suggesting that political conservatism may be a manifestation of a cautious strategy in processing and responding to information that is both timeinvariant and ideologically neutral, and can be manifest even in rapid perceptual decision-making processes. This is relevant to the wealth of novel research on the role of uncertainty in the neural underpinnings of political processes [26,27,31,83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results, therefore, offer a novel addition to this literature by suggesting that political conservatism may be a manifestation of a cautious strategy in processing and responding to information that is both timeinvariant and ideologically neutral, and can be manifest even in rapid perceptual decision-making processes. This is relevant to the wealth of novel research on the role of uncertainty in the neural underpinnings of political processes [26,27,31,83].…”
Section: Discussionmentioning
confidence: 99%
“…A fertile literature has revealed that individuals' ideological inclinations are related to various psychological traits, such as their personal needs for order and structure [3][4][5], cognitive flexibility [6,[14][15][16][17][18], metacognition and learning styles [19,20] and even perceptual reactivity to negative information [21][22][23][24]. The advent of political neuroscience [25], illustrating the neural structures and processes that underpin ( political) ideology [26][27][28][29][30][31][32], spurs even more profound questions about the ways in which cognitive mechanisms may mediate between the brain and belief.…”
Section: Introductionmentioning
confidence: 99%
“…How humans trade-off the prospective benefits of ( preventing) political change against the immediate cost of conflict remains poorly understood. One prominent line of work has related contentious politics to political ideologies and the associated differences in people's moral conviction and cognitive style [9][10][11][12][13][14][15][16][17][18][19][20][21]. Unfortunately, findings are mixed and often limited to specific political issues and contexts [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one may sort plants into groups of fruits or vegetables without needing to sort oneself into a fruit or vegetable group, but to sort other Democrats and Republicans as in-or out-group members, one must first group oneself as either Democrat or Republican. Differential activity in the rAI has also been linked to categorizing ambiguous race faces and political ideology [34]. In a parcellation of the insula, the anterior insula was found to be connected with the anterior cingulate cortex, amygdala and dorsolateral prefrontal cortex [35]; these areas have also been linked to categorization along racial lines [17,36].…”
Section: Neural Correlates Of Social Categorizationmentioning
confidence: 99%